The Educational System and Resistance to Reform: The Limits of Policy - John F. Covaleskie (Arizona State University, 1994)
I suggest some reasons why education has proved so resistant to reform. That the educational system is a system is, in some respects, more significant to this question than the fact that it deals with education; that it is a system militates against certain sorts of reforms being successfully adopted. I will also argue that policymakers' efforts to reform education are made more difficult because of lack of clarity of purpose. Though all agree that "excellence" is the goal to be pursued, there is little attention to the meaning of excellence, nor how we would recognize it if we saw it. Often, "excellence" is used synonymously with "competitiveness." I explore the limits of policy, and suggest that these limits are inescapable. Recognition of these limits may allow us to attend to those policy areas where success may be more likely.